An Overview of Traditional Markets Sanitation in Kupang City - Kondi, Ceria Yulinar Dorkas; Doke, Soni; Sinaga, Masrida (Timorese Journal of Public Health, 2023)
Market sanitation is disease prevention through observation and investigation of market impacts that are directly related to the emergence or spread of a disease. This study aims to describe the hygienic conditions in traditional markets in Kupang City. This type of research is descriptive with a survey design. The research population is traditional markets in the city of Kupang as many as 5 traditional markets. In this study, descriptive analysis is used as an analytical method to describe the hygienic conditions of traditional markets in Kupang City. The results of the study show that the sanitary condition of the availability of clean water for traditional markets in the City of Kupang 2021 is categorized as fulfilling the requirements. While the sanitation conditions of facilities and buildings (handwashing area, trash bins, SPAL, toilets and parking lots), the sanitary conditions of the construction (roof, walls, floors, ventilation and lighting) of traditional markets, the sanitary conditions of animal control of disease transmission or vectors of traditional markets are all This category does not meet health requirements. Suggestions to the local government of Kota Kupang should enact stronger regulations on market management in the private sector to promote a healthy market